Luminescence-colour-changing sensing of Mn2+ and Ag+ ions based on a white-light-emitting lanthanide coordination polymer. Issue 36 (24th April 2017) - Li, Yu-xin; Li, Shang-ju; Yan, Peng-fei; Wang, Xin-yu; Yao, Xu; An, Guang-hui; Li, Guang-ming
Abstract : A white-light-emitting LnCP is effectively applied to the detection of Ag + and Mn 2+ ions with high selectivity and sensitivity via luminescence-colour change. Abstract : The white-light emission of a triple-component lanthanide coordination polymer turns to blue and red upon adding Mn 2+ and Ag + ions, respectively.